Controlled Release of Therapeutics From Enzyme-Responsive Biomaterials - Minehan, Rachel L.; Del Borgo, Mark P. (Frontiers in Biomaterials Science, 2022)
Numerous promising drug leads are often abandoned due to having poor pharmacokinetic profiles. Biomaterials are often used as drug delivery systems to improve the pharmacokinetics of these otherwise promising drug candidates. Hydrogels are a subset of biomaterials that offer porous matrices, permeable to endogenous nutrients in aqueous in vivo environments. Environmentally sensitive hydrogels have become of interest to further tailor these materials to only allow therapeutic release in response to specific environmental cues instead of simple encapsulation and subsequent diffusion. Enzyme-responsive materials allow for the exploitation of endogenous tissue enzyme expression levels and/or altered expression levels during pathological states. The simplest and most common method for stimulus-dependant release is through the destruction of the matrix to release encapsulated therapeutics that would otherwise be trapped indefinitely. A second approach is to covalently attach therapeutics to the hydrogel scaffold and include enzymatically sensitive cross linkages throughout the scaffold backbone. The third, and least common approach, is to use labile linkers between the therapeutic and the scaffold which affords controlled, precise release of the therapeutic with a known molecular structure. These linkers can often be tailored to specific enzymes that are often elevated in certain disease states. This review will; 1) briefly describe matrix degradation; 2) present non-specific cleavage of covalently attached therapeutics and; 3) highlight the few examples of targeted cleavage of therapeutics from specific matrix locations and the potential use of these systems in biomedicine.